Meningkatkan Disiplin Belajar Siswa Kelas 6A di MI Al-Khoiriyyah 2 Semarang Melalui Strategi Pengelolaan Kelas yang Efektif - Kunfaridah, Alifah Dewi (Motekar: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This article discusses the implementation of effective classroom management strategies in improving student learning discipline, supporting and inhibiting factors in effective classroom management strategies, challenges that occur, and whether or not there is an effect of effective classroom management on the learning outcomes of 6A students at MI Alkhoiriyyah 2 Semarang. The method used is a qualitative method with data collection techniques through observation, interviews, and documentation. The results of this study indicate that effective classroom management in improving student learning discipline requires the right strategy. MI Al Khoiriyyah 02 Semarang has two strategies, namely by instilling student learning contracts and paying attention to existing infrastructure. In implementing this strategy there are 2 factors, namely supporting factors and inhibiting factors. The solution in overcoming the obstacles of the strategy by giving sanctions to students.